Feasibility and assessment of self-reported dietary recalls among newly diagnosed multiple sclerosis: a quasi-experimental pilot study - Saxby, Solange M.; Ehlinger, Mary A.; Brooks, Lisa; Titcomb, Tyler J.; Ten Eyck, Patrick; Rubenstein, Linda M.; Bisht, Babita; Shemirani, Farnoosh; Gill, Christine; Kamholtz, John; Snetselaar, Linda G.; Wahls, Terry L. (Frontiers in Nutrition, 2024)
Background: Individuals who are newly diagnosed with clinically isolated syndrome (CIS) or relapsing-remitting multiple sclerosis (RRMS) may choose not to undergo disease-modifying therapies (DMTs) due to concerns about expenses or potential adverse effects. Thus, many individuals will opt for alternative therapies, such as dietary modifications. Among these dietary approaches, the modified Paleolithic elimination diet has shown promise for improving MS-related symptoms; however, restriction of certain food groups can lead to inadequate intake of nutrients. Methods: Three-day self-reported 24-hour dietary recalls using the Automated Self-Administered 24-hour (ASA24) Dietary Assessment Tool were assessed during a 12-month quasi-experimental (i.e., non-randomized) trial among individuals who either voluntarily declined DMTs and received health behavior (HB) intervention, (n=29) or included DMTs and opted for the standard of care (SOC; n=15). Participants in the HB group received a multimodal intervention that included dietary modifications, a walking program, and breathing exercises. Usual intake of each micronutrient was estimated and then evaluated with the estimated average requirement (EAR)-cut point method. Results: At 12 months, >80% of both HB and SOC groups completed 3 days of the self-reported 24-hour recalls, indicating the potential feasibility of ASA24. From baseline to 12 months, the HB group had a decreased mean ratio in total grains (0.64; 95% CI 0.43-0.93; p=0.02) and added sugars (0.52; 95% CI 0.35-0.75; p ≤ 0.001), and an increased mean ratio intake of cured meats (1.74; 95% CI 1.05-2.90; p=0.04); whereas, the SOC group had a decreased mean ratio intake for beef, veal, pork, lamb, and game meat (0.60; 95% CI 0.40-0.90; p=0.01). At baseline, both groups had high proportions with inadequate intake of vitamin E and calcium. The SOC group also had a high proportion with inadequate intake of vitamin D. By 12-months, the HB group exhibited severe proportions of nutrient inadequacies (>20% of the group) for vitamin D (43.5%), vitamin E (29.1%), calcium (69.9%), and copper (27.8%). The SOC group, following their own diet, had inadequacies for all the same micronutrients, except for copper, as the HB group.